Empowering BIPA Educators in Australia through Indonesian Local Wisdom Training - Yulianeta, Yulianeta; Hardini, Tri Indri; Wirza, Yanty; Haerudin, Dingding; Amandangi, Dewi (CV. BImbingan Belajar Assyfa, 2024)
In Australia, Indonesian Language for Foreign Speakers (BIPA) educators have diverse educational backgrounds, including not only bachelor's or master's degrees in teaching Indonesian but also various disciplines such as linguistics and sociology. Interestingly, a number of these educators are native Australians who have mastered Indonesian. This study aims to improve the capacity of BIPA educators by equipping them with local Indonesian wisdom so that they can teach the Indonesian language and culture more effectively. This study uses a qualitative approach with direct training methods and field mentoring, which was carried out at the Indonesian Embassy in Canberra for two days. On the first day, 20 educators were introduced to the concept of local Indonesian wisdom, and on the second day, they practiced teaching using local wisdom-based materials. Data were collected through observation and in-depth interviews with participants. The analysis results showed that after the training, 85% of participants felt more confident in integrating local cultural elements into their teaching, as measured by a post-training survey. In conclusion, this training has successfully empowered BIPA educators by providing additional skills that enable them to teach Bahasa Indonesia more engagingly and contextually. This emphasizes incorporating local cultural elements into language learning to enhance student appeal and understanding. Thus, improving the competence of BIPA educators through this local wisdom training has contributed significantly to Bahasa Indonesia education in Australia.